What is the philosophy of education needed in the XXI century? - Krawczyńska-Zaucha, Tatiana (Kultura-Społeczeństwo-Edukacja, 2020)
The last decades have witnessed constant changes andrefor ms in education in many countries. The paradox of these changes is that they require further changes and transformations and further reforms. Education systems do not correlate with the needs of humanity in the 21st century, nor with the emerging new world view. This article aims to examine education from the global of the world of digitization in which we live and to find an answer to the question what is the purpose of education in the 21st century. From the analyses of different pedagogicaltre nds and philosophical assumptions underlying them, a conclusion will be drawn about the need for a philosophy open to new challenges in today’s educational reality in order to achieve this goal. This article will addresskey issues of the VUCA world concerning education such as digitization, educate to the unknown, the phenomenon of global teenagers and the development of robotics.